The experiences and needs of parents of children with cerebral palsy in coping with the child’s disease - Kadri Kööp; Mare Tupits (Proceedings of the Estonian Academy of Sciences)
Cerebral palsy, which occurs in two to three out of every 1000 live births, has multiple aetiologies resulting in brain injury that affects movement, posture, and balance. A familyâs adjustment to the childâs cerebral palsy is a challenging process, and parents often feel that they have not received adequate explanations on how to care for their child. To ensure the best possible quality of life for the child, the whole family must be taken care of. Supporting family members and understanding their needs facilitates the delivery of high-quality, patient-centred nursing care.